An automated, objective and open source tool for stream threshold selection and upstream riparian corridor delineation. (January 2015) - Bhowmik, Avit Kumar; Metz, Markus; Schäfer, Ralf B.
Abstract: The extraction of stream networks from digital elevation models (DEMs) and delineation of upstream riparian corridors (URCs) for stream sampling points (SSPs) are frequently used techniques in freshwater and environmental research. Selection of an accumulation threshold (AT) for stream extraction and delineation of URCs are often done manually. Two algorithms are introduced in this paper that allow for automated AT selection and URC delineation. ATs are selected to yield the highest overlap of DEM-derived and traditionally mapped streams as well as to assure extraction of all mapped streams from DEMs. URCs are delineated after snapping SSPs to DEM-derived streams. The new tool showed similar or better performance than comparable algorithms and is freely available, interfacing the open source software packages R and GRASS GIS. It will improve the extraction of stream networks and the assessment of magnitude and scale of effects from riparian stressors (e.g. landuse) on freshwater ecosystems. Graphical abstract: Highlights: Automated threshold selection for stream extraction. Goodness of fit of extracted networks with mapped stream networks. Automated delineation of upstream riparian corridors for stream sampling points. Algorithms developed by combining R and GRASS GIS. Computer code and data provided.